login

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 61st year, we have over 378,000 sequences, and we’ve reached 11,000 citations (which often say “discovered thanks to the OEIS”).

Jump Sum Recursion Triangle.
1

%I #58 Jul 17 2020 07:19:49

%S 0,0,1,1,1,4,1,11,-1,1,26,-27,1,57,-289,-1,1,120,-2160,-256,1,247,

%T -13359,-13604,1,1,502,-73749,-383750,3125,1,1013,-378283,-7682623,

%U 1006734,1,1,2036,-1845522,-124221692,126018521,46656

%N Jump Sum Recursion Triangle.

%C The Jump Sum Recursion Triangle is defined as a row by row reading of the coefficients of the recursions satisfied by the error term between Pascal-Triangle j-jump sums and 2^(jm)/j. To clarify this, define the j-jump sum, S(j,n)=Sum_{m= -oo..oo} C(n,jm), with C(x,y) the binomial coefficient if 0<=y<=x and 0 otherwise. It is known that S(1,n)=2^n and S(2,n)=2^(n-1). This suggests the heuristic that S(j,n) is approximately 2^n/j and motivates looking at the integral error terms, jS(j,n)-2^n. So, for fixed j, define the sequence, G(j,m)=G(m)=jS(j,mj)-2^(mj), and let p(j,X) be the characteristic polynomials of the sequence. The Jump Sum Recursion Triangle is defined as a row by row reading of the coefficients of p(1,X), p(2,X), p(3, X), p(4, X)... .

%D Charles Cook and Rebecca Hillman, Some Jump Sum Patterns For the Rows of Pascal's and Related Triangles, Congressus Numerantium, 2010, pp. 255-267.

%D Russell Jay Hendel, Jump Sum Recursions, 16th Fibonacci Conference, Rochester NY, 2014.

%H Michel Marcus, <a href="/A244608/b244608.txt">Table of n, a(n) for n = 1..650</a>

%H John B. Dobson, <a href="http://arxiv.org/abs/1610.09361">A matrix variation on Ramus's identity for lacunary sums of binomial coefficients</a>, arXiv preprint arXiv:1610.09361 [math.NT], 2016.

%F The following theorem can be proved: For j>=3, let w be a primitive j-th root of unity. Let L(k)=Sum_{p=0..j-1} c(p)w^(kp) with c(0)=2 and c(i)=C(j,i) if i>0. Then p(j,X)=(X-L(1))(X-L(2))...(X-L([(n-1)/2])). For example: If j=3, then w is a primitive cube root of unity and [(3-1)/2]=1. We have L(1)=2+3w+3w^2=-1 and X-L(1)=X+1 which is p(3,X) and corresponds to the 3rd row (terms 3 and 4) in the Jump Sum Recursion Triangle.

%e Suppose j=3. Then using our definition, S(3,3)=C(3,0)+C(3,3)=2, S(3,6)=C(6,0)+C(6,3)+C(6,6) = 1+20+1=22 (To explain the name "jump sum," we note, that we don't sum the Pascal Row across, but jump in steps of 3 when taking the sum). G(3,1)=G(1)=3S(3,3)-2^3=-2 and G(2)=3S(3,6)-2^6=2. Clearly, G(2)=-G(1). In fact, the sequence G(m)= G(3,m) - -2,2,-2,2,... - satisfies the recursion G(m)+G(m-1)=0 with characteristic equation X+1. Hence, the 3rd row in the Jump Sum Recursion Triangle is 1,1. Similarly, we can calculate that the sequence G(m)=G(m,4) which is, -8,32,-256,1024,..., which satisfies the recursions G(m)+4G(m-1)=0 with characteristic equation X+4. Hence, the 4th row of the Jump Sum Recursion Triangle is 1,4. Since S(n,1)=2^n and S(n,2)=2^(n-1), we have 1S(n,1)-2^n=0 and 2S(n,2)-2^(n-1)=0 showing that the sequences G(m,1) and G(m,2) satisfy the zero recursion, G(m)=0. Hence the first two rows of the Jump Sum triangle are identically 0.

%e The Jump Sum Triangle starts:

%e 0;

%e 0;

%e 1, 1;

%e 1, 4;

%e 1, 11, -1;

%e 1, 26, -27;

%e 1, 57, -289, -1;

%e 1, 120, -2160, -256;

%e 1, 247, -13359, -13604, 1;

%e 1, 502, -73749, -383750, 3125;

%e ...

%o (PARI)

%o /* Function CreateTriangle produces first r rows of the Jump Sum Recursion Triangle*/

%o CreateTriangle(r) ={

%o /* First two rows created manually */

%o print(1, " ", [0]);

%o print(2, " ", [0]);

%o /* Create r rows of Pascal's triangle: m[i,j]= C(i,j)*/

%o m=matrix(r,r,i,j,0);

%o m[1,1]=1;

%o m[1,2]=1;

%o for(i=2,r,m[i,1]=1);

%o for(i=2,r,for(j=2,r,m[i,j]=m[i-1,j]+m[i-1,j-1]));

%o /*Loop to create rows 3,4,5,...,r of Jump Sum Recursion Triangle */

%o for(o=3,r,

%o /* We create a modified Binomial Coefficient Circulant Matrix,n. The first row of n is 2,C(o,2),C(o,3),..., C(o,o-1). To motivate this we extend our definitions above as follows:Define S(j,n,k)=Sum_{m=-oo..oo} C(n,k+jm), define G(m,k)=jS(j,mj,k)-2^(mj), and define G(m)= <G(m,0), G(m,1),...,G(m,j-1)>. Then n*G(m) = G(m+1). This gives a matrix representation for the sequence G. The j-th row of the Jump Sum Recursion Triangle which are the coefficients of the recursion satisfied by G is equal to the minimal polynomial satisfied by n. Hence we can print out the triangle by printing out the coefficients of the minimal polynomials*/

%o n=matrix(o,o,i,j,0);

%o for(i=1,o,n[i,i]=2);

%o for(j=1,o-1,for(i=1,o-j,n[i,i+j]=m[o,o+1-j]));

%o for(i=2,o,for(j=1,i-1,n[i,j]=m[o,o+1-i+j]));

%o /* Construct minimal polynomial by multiplying all factors

%o without multiplicity and avoiding factors X-2^n and X */

%o f=factor(charpoly(n));

%o g=length(f[,1]);

%o h=1;

%o for(i=2,g,if(f[i,1]==x,h,h=h*f[i,1]));

%o print(o," ",Vec(h));

%o )};

%o /*The first 11 rows of the Jump Sum Recursion Triangle, listed in the DATA step, can be obtained by calling CreateTriangle with argument r=11.*/

%o CreateTriangle(11);

%K sign,eigen,easy,tabf

%O 1,6

%A _Russell Jay Hendel_, Jul 01 2014